Nogo-receptors NgR1 and NgR2 do not mediate regulation of CD4 T helper responses and CNS repair in experimental autoimmune encephalomyelitis. - Karin Steinbach; Claire L McDonald; Markus Reindl; Rüdiger Schweigreiter; Christine Bandtlow; Roland Martin (PLoS ONE)
Myelin-associated inhibition of axonal regrowth after injury is considered one important factor that contributes to regeneration failure in the adult central nervous system (CNS). Blocking strategies targeting this pathway have been successfully applied in several nerve injury models, including experimental autoimmune encephalomyelitis (EAE), suggesting myelin-associated inhibitors (MAIs) and functionally related molecules as targets to enhance regeneration in multiple sclerosis. NgR1 and NgR2 were identified as interaction partners for the myelin proteins Nogo-A, MAG and OMgp and are probably mediating their growth-inhibitory effects on axons, although the in vivo relevance of this pathway is currently under debate. Recently, alternative functions of MAIs and NgRs in the regulation of immune cell migration and T cell differentiation have been described. Whether and to what extent NgR1 and NgR2 are contributing to Nogo and MAG-related inhibition of neuroregeneration or immunomodulation during EAE is currently unknown. Here we show that genetic deletion of both receptors does not promote functional recovery during EAE and that NgR1 and NgR2-mediated signals play a minor role in the development of CNS inflammation. Induction of EAE in Ngr1/2-double mutant mice resulted in indifferent disease course and tissue damage when compared to WT controls. Further, the development of encephalitogenic CD4(+) Th1 and Th17 responses was unchanged. However, we observed a slightly increased leukocyte infiltration into the CNS in the absence of NgR1 and NgR2, indicating that NgRs might be involved in the regulation of immune cell migration in the CNS. Our study demonstrates the urgent need for a more detailed knowledge on the multifunctional roles of ligands and receptors involved in CNS regeneration failure.